Fifteen-minute consultation: How to be the paediatrician at a trauma call. Issue 1 (14th June 2019) - Begley, Roisin; Martin, Philip Aidan; Morgan, Jeff; Roberts, Zoe; Mullen, Stephen
Abstract : The management of paediatric trauma patients can be complex, involving a coordinated multidisciplinary approach. Paediatricians form an integral part of the trauma team and are often tasked with managing circulation. In this article, we will discuss the assessment of catastrophic haemorrhage and 'circulation' through the viewpoint of a paediatrician via a case discussion. This will include initial investigations and management, noting the time critical nature in identifying and stopping catastrophic haemorrhage. The discussion will comment on how to address hypovolaemic shock and touch on the role of imaging.